Pathophysiology and mechanisms of hearing impairment related to neonatal infection diseases - Capra, Daniela; DosSantos, Marcos F.; Sanz, Carolina K.; Acosta Filha, Lionete Gall; Nunes, Priscila; Heringer, Manoela; Ximenes-da-Silva, Adriana; Pessoa, Luciana; de Mattos Coelho-Aguiar, Juliana; da Fonseca, Anna Carolina Carvalho; Mendes, Carmelita Bastos; da Rocha, Lanni Sarmento; et al. (Frontiers in Microbiology, 2023)
The inner ear, the organ of equilibrium and hearing, has an extraordinarily complex and intricate arrangement. It contains highly specialized structures meticulously tailored to permit auditory processing. However, hearing also relies on both peripheral and central pathways responsible for the neuronal transmission of auditory information from the cochlea to the corresponding cortical regions. Understanding the anatomy and physiology of all components forming the auditory system is key to better comprehending the pathophysiology of each disease that causes hearing impairment. In this narrative review, the authors focus on the pathophysiology as well as on cellular and molecular mechanisms that lead to hearing loss in different neonatal infectious diseases. To accomplish this objective, the morphology and function of the main structures responsible for auditory processing and the immune response leading to hearing loss were explored. Altogether, this information permits the proper understanding of each infectious disease discussed.